The Organization of Words in Mental Lexicon: Evidence from Word Association Test - Budi Eko Pranoto; Lidia K. Afrilita (Universitas Teknokrat Indonesia, 2018)
Both in psychology and linguistics studies, memory is one of the core of interests amongst researchers. In linguistics, memory is the place where language processes consisting of language perception, storage, and access of words take place. Words, in memory, are stored in complex, clear, well-organized, and ordered networks called nodes, which can be represented by World Wide Web. This word organization in psycholinguistics is referred to mental lexicon. This study aims to investigate what kind of nodes representation stored in mental lexicon of foreign language learners. Word Association Test (WAT), the well-known study method in both psychology and linguistics studies, is employed by using English Swadesh word list as the stimulus to elicit the lexical relation amongst words. The basic principle of the test is giving a stimulus to respondents and asking them to give the very first word coming out of their mind. Respondents are undergraduate students of English Literature a university in Indonesia. Findings of this research support the previous findings stating that non-native speakers tend to make syntagmatic relation, which is mostly dominated by collocation association. Interestingly, the finding also shows that the words network in mental lexicon involves a dynamic development based on experience and perception of the respondents.Key Words: lexical relation, mental lexicon, word association